Principles, Practice, and Policy Problems in the Financing of Higher Education in India (International Journal of Innovative Research in Engineering & Management, 2023)
Due to theoretical and practical issues,  funding advanced learning in India has been a difficult  task. It has mainly been a government-funded endeavor,  with the government bearing about three-quarters of the  entire cost. Non-government sources of revenue, such as  fees and voluntary donations, have been decreasing in  recent years. At the similar moment, the secondary  educational sector is undergoing a transformation.  demands have been steadily increasing. It is becoming  clearer that public finances will not be able to properly  support higher education, especially while public school  systems are struggling to meet even basic requirements. As  a result, many policy suggestions have been proposed  recently, including 'privatization.' This essay examines  these ideas critically and contends that India's The higher  educational sector isn't ready for "privatization" yet.'  Simultaneously, the importance of experimenting with a  variety of options, such as It is emphasized the importance  of college tuition, students financing, graduation tax, and  privatisation in generally.
Keywords: Education Sector; Higher Education; Policy Problem; Political Development; Scientific Foundation